ECONOMIC SECURITY OF A TECHNICAL UNIVERSITY: CONCEPTUAL BASES - Sergey M. Dmitriev; Mikhail V. Shiryaev; Sergey N. Mityakov (Moscow Polytechnic University, 2016)
The article opens a cycle of publications by the title "Economic security of the technicaluniversity".The paper focuses on the questions connected with expediency of introduction of a control system of economic security in a technical university. The term "economic security of the technical university" is defined as a "state of university's economic potential, which ensures the defense of its economic interests, the safety of the workers and students, and the effective development of theuniversity in accordance with its mission even under adverse external and internal conditions". The article also views the aspects of economic security (students, teachers, science and innovations, financial, material and information resources, management), and the main calls and threats for technical university in modern conditions.